Creating Materials for Students in EFL Teaching through Flipped Learning - Baybabaeva Shoiraxon Ismatovna (Research Parks Publishers, 2022)
The technologies of mixed and “inverted” (flipped classroom) learning are considered, which ensure the development of a student as a subject of self-educational activity and form his readiness for self-development in the future. The key characteristics of blended learning are highlighted. The process of